Engineered nanomaterials and their surface functionalization for the removal of heavy metals: A review. (February 2020) - Jawed, Aquib; Saxena, Varun; Pandey, Lalit M.
Highlights: Various nanomaterials explored as efficient adsorbents for heavy metals are deliberated. Crosslinking, chelation and electrostatic interactions assisted heavy metals removal. Surface functionalization of adsorbent has enhanced adsorption capacity by many folds. Strategies to evade the toxic effects of nanomaterials for adsorbents are highlighted. Potentials, limits and scopes of nanomaterials for heavy metal removal are outlined. Abstract: Water is polluted by various harmful toxic chemical substances, precisely heavy metals, dyes, and pathogens, which have a disastrous effect on the ecological balance of human as well as animal life. Therefore, there is an urgent need for new technologies to remove these noxious pollutants from water/wastewater. Adsorption is one of the predominant method among all the reported techniques for the removal of heavy metals. Nano technological applications in this direction, i.e. development of nano-sized materials, tubes and composites as adsorbents have engrossed rapidly. In this review, current trends of nanomaterials for the removal of heavy metals from water/wastewater are concisely discussed. Applications of different engineered nanomaterials based on iron oxide, titanium oxide, silica, carbon, graphene oxide, and bio-nanomaterials are largely focused. Different strategies and surface modifiers have been used for the surface modifications/functionalization of these nanomaterials, which in turn enhanced the adsorption capacities by many folds. Toxic effects of various nanoparticles are also discussed, and various strategies like embedding, encapsulation to prevent their releases into the environment are deliberated. In addition, the selection of NPs for the removal of various metals has also been discussed in the respective sections. This review will provide an insight into the latest researches, which is expected to offer worthy implications to academicians and industry professionals working in environmental engineering domain for the removal of heavy metals from water/wastewater.